Physiological and pharmacological stimulation for in vitro maturation of substrate metabolism in human induced pluripotent stem cell-derived cardiomyocytes - Colleen A. Lopez (Nature Portfolio, 2021)
Abstract Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) enable human cardiac cells to be studied in vitro, although they use glucose as their primary metabolic substrate and do not recapitulate the properties of adult cardiomyocytes. Here, we have explored the interplay between maturation by stimulation of fatty acid oxidation and by culture in 3D. We have investigated substrate metabolism in hiPSC-CMs grown as a monolayer and in 3D, in porous collagen-derived scaffolds and in engineered heart tissue (EHT), by measuring rates of glycolysis and glucose and fatty acid oxidation (FAO), and changes in gene expression and mitochondrial oxygen consumption. FAO was stimulated by activation of peroxisome proliferator-activated receptor alpha (PPARα), using oleate and the agonist WY-14643, which induced an increase in FAO in monolayer hiPSC-CMs. hiPSC-CMs grown in 3D on collagen-derived scaffolds showed reduced glycolysis and increased FAO compared with monolayer cells. Activation of PPARα further increased FAO in cells on collagen/elastin scaffolds but not collagen or collagen/chondroitin-4-sulphate scaffolds. In EHT, FAO was significantly higher than in monolayer cells or those on static scaffolds and could be further increased by culture with oleate and WY-14643. In conclusion, a more mature metabolic phenotype can be induced by culture in 3D and FAO can be incremented by pharmacological stimulation.